2019
DOI: 10.1016/j.jeurceramsoc.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort-pulsed laser machining of dental ceramic implants

Abstract: A novel approach for machining of cylindrical hard materials and arbitrary shapes is presented. Alumina-toughened zirconia dental implants with complex geometry are manufactured with femtosecond quasi-tangential laser ablation. This rapid prototyping approach for small-scale production decreases the development-time cycle tremendously and trumps conventional approaches. Moreover, a competitive parameter study for radial and tangential ablation with single and multi-pulse is presented. A process achieving an ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 26 publications
2
18
0
3
Order By: Relevance
“…And similarly to what was attempted in monolithic zirconia, laser-modifications of alumina-zirconia composites were used to induce osteogenic differentiation of human mesenchymal stem cells [20] and favour viability of osteoblast-like cells [21], or to help osseointegration of endosseous dental implants [22]. In addition to the microstructural changes induced in zirconia by the melting/ablation/quenching sequence, alumina-zirconia composites show also chemical changes, as reported by Ackerl et al [18] who reported that "Alumina […] seemed to dissolve approaching the surface".…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…And similarly to what was attempted in monolithic zirconia, laser-modifications of alumina-zirconia composites were used to induce osteogenic differentiation of human mesenchymal stem cells [20] and favour viability of osteoblast-like cells [21], or to help osseointegration of endosseous dental implants [22]. In addition to the microstructural changes induced in zirconia by the melting/ablation/quenching sequence, alumina-zirconia composites show also chemical changes, as reported by Ackerl et al [18] who reported that "Alumina […] seemed to dissolve approaching the surface".…”
Section: Introductionmentioning
confidence: 83%
“…Femtosecond laser was used to machine dental ceramic implants made of zirconia-toughened alumina (ZTA) [18], or to induce regular patterns on an alumina-toughened zirconia (ATZ) surface [19]. And similarly to what was attempted in monolithic zirconia, laser-modifications of alumina-zirconia composites were used to induce osteogenic differentiation of human mesenchymal stem cells [20] and favour viability of osteoblast-like cells [21], or to help osseointegration of endosseous dental implants [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have performed extensive material characterization on hard ceramics modified by femtosecond laser, aiming at dental implants applications [21,33,40]. On Zirconia, Stanciuc et al developed arrays of pits with different spacing, diameter and depth to evaluate human mesenchymal stem cells migration (hMSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Femtosecond laser machining has already been proposed as an innovative technique to create topographical features on the surface of ceramics, commonly used in the fields of optical and refractory materials. Some studies have reported the use of femtosecond laser to texture the surface of hard ceramics [19][20][21], although little work has been conducted on periodic surface structuring, particularly with the intent of implants development, with scarce results available on the biological response to these materials [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Defined ablation conditions are a prerequisite for low roughness and efficient laser ablation [7]. In principle the fluence, laser repetition rate, and scan speed are interdependent [8] and no global optimum can be reached. However, depending on the desired process either high material removal rate or surface quality can be reached for 2.5D orthogonal strategies.…”
Section: Introductionmentioning
confidence: 99%